Dépression et affection dans Le juste milieu d’Annabel Lyon : une poétique du care - Maite Snauwaert (Atlantis)
Abstract In her elegant and raw novel, The Golden Mean, English-Canadian author Annabel Lyon revisits a founding cultural figure of Western thought through the fluctuating affects of mental illness. Approaching Aristotle in the light of depression and bipolarity, and opting for the strong choice of first person and present tense, she humanizes and actualizes the philosopher as a living, suffering being. The historical novel becomes the ground for a demonstration of empathy, in which the portrayal of the teaching relationship has overtones of contemporary care ethics.